No fluxo do Anhembi-tietê: o rio e a colonização da capitania de São Vicente nos séculos XVI e XVII - José Carlos Vilardaga (Nuevo mundo - Mundos Nuevos, 2020)
This article aims to analyze the Anhembi River, called Tietê after the 18th century, highlighting its fundamental importance for the settlement of indigenous populations and, later, of the colonial society installed from the 16th century on the Piratininga Plateau. This region was the centre of a wide hydrographic network and formed by floodplains, fields and hills, located after Serra do Mar, a mountain range close to the coast. On the plateau, taking advantage of a dense Tupi presence and their accumulated knowledge, Jesuits and settlers gradually settled through alliances, wars, enslavement and miscegenation, forming the village of São Paulo (Captaincy of São Vicente). The Anhembi River and its tributaries would guarantee food, water and circulation. Both downstream and upstream, the river served the expansion processes of the São Paulo nucleus, expanding its area of influence and forming a colonial spatiality, in which it acted as a structuring axis. In addition, the river allowed peaceful and conflictive relations with the Spanish areas of America, located in the interior, overlapping colonial relations over the relations between Tupi and Guarani. Thus, following the flow of the river, which flows west from Serra do Mar, the colonial space structured in a continuum that articulated the coast, the plateau and the hinterland.